HUBUNGAN TINGKAT KECEMASAN DENGAN MEKANISME KOPING PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RUANGAN HEMODIALISA RUMAH SAKIT GRANDMED LUBUK PAKAM - Sari Desi Esta Ulina Sitepu; Ade viaulina; Selamat Tuahta Sipayung; Pratiwi Christa Simarmata; Junita Ika Susanti Br Ginting (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Chronic renal failure is a disorder in which the body’s ability renal function failed to maintain metabolism, fluid and electrolyte balance. Hemodialysis is a process used patients in a state of acute illness requiring long-term therapy. The patients with renal failure often experience fear because of the conditions they experienced pain this can be a physical stressor that can lead patients to levels of stress and anxiety. Research design using cross- sectional. The population includes hemodialysis patients of Grandmed Hospital Lubuk Pakam. Samples consisting of 43 respondents meeting inclusion criteria were selected using purposive sampling method.This study presented based on the frequency and characteristics of respondents with results of the appointment that anxiety levels can be categorized as mild anxiety (18,6%), moderate anxiety ( 41,9%), and severe anxiety (39,5%). For coping mechanisme of adaptive coping (39,5%) and maladaptive coping (60,5%) category. Analysis of this research data using chi-Square. The results showed that there was an association of anxiety level with coping mechanism in patients with chronic renal failure who underwent hemodialysis at Grandmed Hospital Lubuk Pakam with p = 0,031. The more adaptive the respondent’s clutch the lighter the level of anxiety experienced. The results of this study was expected to nurse or hemodialysis officers further improve the provision of counseling to patients hemodialysis so that patients are able use adaptive coping in the face of anxiety.